Preliminary Calculation of the Energy Budget of the Radio Lines Orbital Method of Monitoring of Incidents caused by the Operator of the GLONASS system - Mikhail Yurievich Senatorov; Ruslan Bogdanovich Syatkovskiy (Безопасность информационных технологий, 2013)
The calculation of the power transmitter onboard GLONASS satellites is submitted for the operation method of orbital monitoring of incidents caused by the system operator. Article is devoted to the description of actual ways of possible distribution of malwares such, as “Easter eggs”, client network applications (torrent-client) and service of digital distribution. As the experiment description on distribution of malwares is provided in the simulated virtual network by means of service of digital distribution. Rules on safety of the user computers in a network are developed.